Relaciones interpersonales y el clima organizacional en la Municipalidad Provincial de Loreto, Nauta 2020 - Arévalo Vásquez, Luz Margarita (2022)
The objective of this study was to determine the relationship between interpersonal relationships and the organizational climate of the Provincial Municipality of Loreto, Nauta - 2020, since it was a descriptive - correlational and non-experimental design investigation, since it was based on observation of the behavior of the variables in their natural context and later they were analyzed, for this a sample made up of 93 collaborators was taken, being surveyed through a 30-item questionnaire, obtaining as results that interpersonal relationships in the Provincial Municipality of Loreto- Nauta presented several deficiencies, because the respondents indicated that they almost never put empathy into practice, communication between colleagues is inefficient, causing that there is no camaraderie in the institution; Similarly, the behavior of their peers does not generate trust. On the other hand, the organizational climate was determined to be deficient, since the collaborators consider that their work and effort is not valued by their boss, nor do they give them autonomy to make their own decisions, in addition, the institution almost never carries out fellowship activities or they receive support from their peers for the development of work activities or for some personal problem. In general, it was determined that there is a significant relationship between interpersonal relationships and the organizational climate of the Provincial Municipality of Loreto, Nauta in the year 2020, this has been proven by a significance of 0.000 with respect to the p-value of 0.05 ; positive and considerable relationship of 0.875.